Motivation for doctors to enter the communities of sisters of mercy - Anastasia Kharitonova (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2023)
The article «Motivation for doctors to enter the communities of sisters of mercy» discusses the possible reasons for the admission of doctors to the communities of sisters of mercy that have been operating on the territory of the Russian Empire since the middle of the 19th century. The communities were unique private charitable organizations that had as their goal the training of new female medical personnel. The reasons are identified by studying the conditions of service of doctors in the communities, which are reflected in the regulatory and office documents. This is material support, social benefits provided to doctors, awards, material for conducting medical practice and medical research. The reasons recorded in some sources of personal origin are also called. The article takes into account the historical context of the existence of doctors. Namely, the statements of representatives of the medical staff of the late XIX - early XX centuries about their financial situation, which had a negative connotation, and their assessment of the quality of training of medical personnel at the medical faculties of Russian universities. The study draws attention to the staff of doctors, their age, experience. The determined motives for entering the communities are correlated with the categories (identified by age, professional level, social status) of doctors. The result of the study is the following statements. Young doctors of the community were given the opportunity to get a job in the capital and a good medical practice. For older and more experienced doctors, the motives for getting a job in these communities were the rights of the civil service. They might also have been attracted to the idea of philanthropy from the communities of sisters of mercy and the communication and cooperation with influential representatives of high society. In addition, the research work developed in the communities attracted doctors of different ages and levels of professionalism.